ISSUES THAT REQUIRE CREATIVE RESEARCH WHEN WORKING WITH GIFTED STUDENTS, IN THE FORMATION OF THEIR COGNITIVE ACTIVITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The summary: This article is devoted to the stages of solving problems requiring creative research when working with gifted students, the formation of their educational activities.